Systematic analysis of proton pump inhibitors-related adverse reactions using the FDA adverse event reporting system database - Zhenyu Wang; Jianan Jin; Guimei Wang; Guoqi Zhou; Hanliang Jiang (PLoS ONE, 2026)
Background Proton pump inhibitors (PPIs), known for their potent acid-suppressing effects, are widely used in various clinical settings, including treatment and prevention. Understanding their adverse effects is crucial. This study, utilizing the FDA Adverse Event Reporting System (FAERS) database, comprehensively analyzes PPI-related adverse events to guide clinical medication practices. Methods This study analyzed suspected adverse drug reactions (ADRs) related to specific PPI drugs using data from the FAERS database, covering Q1 2004 to Q4 2024. Multiple statistical methods, including ROR, PRR, IC025, and EBGM, were employed for evaluation, with ADRs defined according to System Organ Class (SOC) and Preferred Term (PT). A comparative analysis was conducted to assess potential differences in ADR profiles among different PPI drugs. Results This study analyzed 176,680 cases of PPI-related adverse events, with a total of 632,468 adverse reaction reports recorded when PPIs were designated as the primary suspected drug (PS). PPIs showed significantly elevated risks in the renal/urinary and gastrointestinal systems, with other common adverse reactions including hypomagnesemia, hypocalcemia, and renal anemia. Most adverse reactions occurred either within the first 0–30 days of use or after prolonged exposure (>6 months), and elderly patients (≥65 years) were disproportionately affected. Conclusions For high-risk populations using PPIs long-term (such as elderly patients or those with pre-existing renal impairment), continuous monitoring is essential to mitigate potential complications. Unnecessary use should be strictly avoided, and long-term medication should be minimized to ensure safety and appropriateness.